Bagaço de cana-de-açúcar: análise térmica e energética de biomassa - Arantes, Danilo Campiom (2014)
The dependence of fossil fuels is still very evident and the search for alternative environmentally fuels that can reduce this dependency need investment. In this sense, biomass has an important role as a renewable energy source quite exploited on our planet. However, the use of this fuel requires careful and conscientious handling of natural resources, preventing environmental imbalance and destruction of ecosystems. Among the alternatives of biomass for energy purposes, highlights the energetic reuse of forest, agricultural and urban residues. However, this kind of biomass presents low energy efficiency due to certain characteristics that restricts their direct use as fuel, such as low density, high moisture, irregular grain size, low calorific value, high ash, among others. In order to fix some properties, improve and standardize the product is necessary the use of industrial processes, such as compaction and roasting. In this context, this paper is to analyze and define the energy potential of sugarcane bagasse, a large sugarcane mill in the state of Goiás. The experiments were conducted according national standards and consisted perform immediate analysis, determine the density of sugarcane bagasse and define the relationship between calorific value and moisture of the standard product. Finally, we applied the thermal treatment called roasting, which provided energy recovery product and decreased its hygroscopic character when compared to standard product.